Strengthening Motivation Through Group Guidance to Increase Students’ Interest in Continuing Their Studies at Madrasah Mu’allimin Muhammadiyah - Mutakin, Deden (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Continuing studies at the same level of education is an important indicator of the success of student development at Madrasah Mu'allimin Muhammadiyah Yogyakarta. Initial findings indicate that some students in class 3J (Tsanawiyah) are hesitant to continue their studies to the MA level, suggesting a motivation issue that needs to be addressed immediately. Objective: This study aims to strengthen student motivation to increase their interest in continuing their studies through Group Guidance services. Method: This study used a Classroom Action Research approach, grounded in Kurt Lewin's model, implemented in two cycles comprising the planning, action, observation, and reflection stages for 30 students. Data were collected through questionnaires, observations, and counselling anecdotal notes, then analysed descriptively and comparatively between cycles. Results: There was a significant decrease in the number of students who were unsure about continuing their studies, from 50 per cent in the pre-cycle to 30 per cent in Cycle I, and 3.3 per cent in Cycle II. Conclusion: Strengthening motivation through Group Guidance proved effective in increasing students' interest in continuing their studies, especially when implemented in a structured manner and supported by multi-party collaboration. Contribution: This study offers an applicable, systematic, and contextually grounded guidance intervention model to strengthen student continuity of study by integrating motivation-strengthening between schools and families.